A 10‐year longitudinal follow‐up study of a U.K. paediatric transplant population to assess for skin cancer. (1st December 2018) - Foo, S.H.; Nightingale, P.G.; Gazzani, P.; Bader, E.; Ogboli, M.; Martin‐Clavijo, A.; Milford, D.V.; Kelly, D.A.; Moss, C.; Thomson, M.A.
Summary: Background: Our earlier study, published in 2004, 1 found no skin cancer in a cohort of paediatric organ transplant recipients (POTRs) 5–16 years post‐transplantation. We re‐evaluated the same cohort 10 years later. Objectives: To determine the prevalence of premalignant and malignant skin lesions and identify known risk factors associated with melanocytic naevi in a U.K. paediatric transplant population. Methods: Ninety‐eight POTRs from the original 2004 study were invited to participate in this longitudinal follow‐up study. History of sun exposure, demographics and transplantation details were collected using face‐to‐face interviews, questionnaires and case note reviews. Skin examination was performed for regional count of malignant lesions, benign and atypical naevi. Results: Of the 98 patients involved in the initial study, 45 POTRs (eight kidney, 37 liver), with a median follow‐up of 19 years (range 15–26 years), agreed to participate. Neither skin cancer nor premalignant lesions were detected in these patients. When compared with the 2004 cohort, 41 patients in our current cohort had increased numbers of benign naevi ( P < 0·001) with 11 patients having ≥ 50 benign naevi. Seventy‐one per cent of benign naevi in our 2014 cohort occurred on sun‐exposed sites (13% head/neck, 35% arms and 23% legs). Patients who regularly used sunscreen had more benign naevi on their arms ( P = 0·008). Conclusions: Although skin cancer was not observed in our cohort, we identified a significant increase in the number of benign naevi, particularly in those reporting frequent sunburn and sunscreen use.